Measuring Hearing Aid Satisfaction in Everyday Listening Situations: Retrospective and In Situ Assessments Complement Each Other - Lelic, Dina; Wolters, Florian; Schinkel-Bielefeld, Nadja (Journal of the American Academy of Audiology, 2024)
Background Recently, we developed a hearing-related lifestyle questionnaire (HEARLI-Q), which asks respondents to rate their hearing aid (HA) satisfaction in 23 everyday listening situations. It is unknown how HA satisfaction on the retrospective HEARLI-Q scale compares with HA satisfaction measured on the same scale implemented in Ecological Momentary Assessment (EMA).Purpose To learn how retrospective (HEARLI-Q) and in situ (EMA) assessments can complement each other.Research Design An observational study.Study Sample Twenty-one experienced HA users.Data Collection and Analysis The participants first filled out the HEARLI-Q questionnaire, followed by a 1-week EMA trial using their own HAs. HA satisfaction ratings were compared between the two questionnaires and the underlying drivers of discrepancies in HA satisfaction ratings were evaluated.Results HA satisfaction ratings were significantly higher in EMA for speech communication with one or several people. Hearing difficulty in these situations was rated higher in HEARLI-Q than in EMA, but occurrence of those difficult listening situations was also rated to be lower. When comparing only the situations that occur on daily or weekly basis, the two questionnaires had similar HA satisfaction ratings.Conclusions Lower occurrence of difficult listening situations seems to be the key driver of discrepancies in HA satisfaction ratings between EMA and HEARLI-Q. The advantage of EMA is that it provides insight into an individual's day-to-day life and is not prone to memory bias. HEARLI-Q, on the other hand, can capture situations that occur infrequently or are inconvenient to report in the moment. Administering HEARLI-Q and EMA in combination could give a more holistic view of HA satisfaction.
Keywords: hearing aid satisfaction; EMA; retrospective report